Influence of franchisee selection criteria on outcomes desired by the franchisor - Jambulingam, Thani; Nevin, John R. (Journal of Business Venturing, 1999)
Agency theory suggests that an efficient contract between a franchisor (principal) and a franchisee (agent) could be established by the use of selection criteria that would screen prospective franchisees based on their likely future outcomes desired by their franchisors. Franchisors can use franchisee selection criteria as a key input control to enhance the outcomes of their future franchisees. This article examines the relationship between key franchisee selection criteria such as franchisees’ financial capability, experience and management skills, demographic characteristics, attitude toward business dimensions (perceived innovativeness, desire for personal development, seek work-related challenges, personal commitment to the business, and business risk-taking), and key measures of outcomes desired by franchisors (perceived cooperation, satisfaction with the business decision, and franchisee opportunism). The findings show that certain franchisee attitudes toward business can be used as an effective input control strategy by franchisors because they explain a substantial portion of the variance in franchisees’ outcome desired by franchisors.